2020
DOI: 10.3390/rs12101621
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the Detection of Irrigation Events on Maize Plots Using Sentinel-1 Soil Moisture Products

Abstract: Although the real timing and flow rates used for crop irrigation are controlled at the scale of individual plots by the irrigator, they are not generally known by the farm upper management. This information is nevertheless essential, not only to compute the water balance of irrigated plots and to schedule irrigation, but also for the management of water resources at regional scales. The aim of the present study was to detect irrigation timing using time series of surface soil moisture (SSM) derived from Sentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 61 publications
8
40
0
Order By: Relevance
“…However, as optical imagery is affected by cloud cover, the performance of the crop mapping with such data can be reduced in some cases, particularly for temperate or tropical areas [33] . Other recent studies [34][35][36][37][38][39] have shown that the joint use of optical and radar data improves the robustness of the mapping methods [21,35,37]. Nevertheless, all the studies mentioned above deal with the mapping of irrigated areas in arid or semi-arid climatic areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, as optical imagery is affected by cloud cover, the performance of the crop mapping with such data can be reduced in some cases, particularly for temperate or tropical areas [33] . Other recent studies [34][35][36][37][38][39] have shown that the joint use of optical and radar data improves the robustness of the mapping methods [21,35,37]. Nevertheless, all the studies mentioned above deal with the mapping of irrigated areas in arid or semi-arid climatic areas.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, an extensive temporal dataset is still required for the detection of all irrigation events occurring at plot scale. In addition, over irrigated maize plots of southwest France, La page et al [31] investigated the potential of the S 2 MP (Sentinel-1/Sentinel-2-derived soil moisture product [24]) to detect irrigation events at plot scale. The S 2 MP is a soil moisture estimation product mainly derived by coupling Sentinel-1 SAR data and Sentinel-2 optical data using the neural network [24,32].…”
Section: Introductionmentioning
confidence: 99%
“…Th radiation correction for the four bands was performed using the ENVI 5.3 software to convert the digital number (DN) of the images to the surface spectral reflectance. The atmospheric correction was conducted using the FLAASH Atmospheric Correction toolbox using the ENVI software [44,47,[52][53][54][55]. After atmospheric correction, the images were geo-referenced based on 25 ground control points.…”
Section: Gf-1 Datamentioning
confidence: 99%
“…Fortunately, the development of remote sensing technology has led to an effective solution to this problem. Published studies confirmed that the VWC has a significant correlation with the vegetation indices obtained from remote sensing datasets [55][56][57][58][59][60]. The vegetation indices often used to estimate the VWC include the normalized difference vegetation index (NDVI), normalized difference water index (NDWI), enhanced vegetation index (EVI), difference vegetation index (DVI), and ratio vegetation index (RVI) [61][62][63][64].…”
Section: Vegetation Water Content Estimation Modelmentioning
confidence: 99%
See 1 more Smart Citation